Empire, development & colonialism the past in the present - Duffield, Mark R.; Hewitt, Vernon Marston 1961- (Boydell & Brewer, 2009)
The parallels between the language of nineteenth-century liberal imperialism and the humanitarian interventionism of the post-Cold War era are striking. The American military, both in Somalia in the early 1990s and in the aftermath the Iraq invasion, used ethnographic information compiled by British colonial administrators. Are these interconnections, which are capable of endless multiplication, accidental curiosities or more elemental? The contributors to this book articulate the belief that these comparisons are not just anecdotal but are analytically revealing. From the language of moral necessity and conviction, the design of specific aid packages; the devised forms of intervention and governmentality, through to the life-style, design and location of NGO encampments, the authors seek to account for the numerous and often striking parallels between contemporary international security, development and humanitarian intervention, and the logic of Empire. MARK DUFFIELD is Professor of Development Politics at the University of Bristol; VERNON HEWITT is Senior Lecturer in Politics at the University of Bristol